HYPOLIPIDEMIC POTENTIAL OF METHANOLIC EXTRACT OF GRACILARIA CORTICATA ON STREPTOZOTOCIN-INDUCED DIABETIC RATS - Subashini, Sekar; Kripa, Kavasseri Ganesan; Pugalendi, Kodukur Viswanathan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objectives: Diabetes mellitus is associated with profound alterations in the levels of plasma lipids and the lipoprotein profile. Herbs and herbal drug preparations find wide use in alleviating the complications of uncontrolled diabetes owing to their low cost and lesser side effects. This study was aimed at establishing the hypolipidemic effect of methanolic extract of sea weed Gracilaria corticata on streptozotocin (STZ)-induced diabetic rats. Methods: STZ-induced Wistar male albino rats were administered with methanolic extract of Gracilaria corticata (MGC) at a dosage of 100 mg/kg BW/day per orally for 45 days. Glibenclamide (600 Î¼g/kg BW/day) administered rats served as standard drug control. Animals were sacrificed on 46th day, biochemical parameters associated with lipid metabolism were analyzed in blood and tissue samples, statistical significance determined. Results: Elevated levels of total cholesterol, triglycerides, and free fatty acids were observed in the plasma and tissues of diabetic rats as compared to MGC and glibenclamide treated groups. The diabetic rats also had elevated levels of low-density lipoprotein (LDL-C) and very low-density lipoprotein (VLDL-C) and decreased levels of high-density lipoprotein (HDL-C) while the MGC and glibenclamide treated rats showed near normal levels of these indices. Conclusion: This study establishes the hypolipidemic potential of MGC in STZ-induced diabetic rats. Keywords: Gracilaria corticata, Diabetes mellitus, Hypolipidemic, Streptozotocin.